Final answer:
To find (s∘t)(-7), first calculate t(-7), which is -21, then apply s to get s(-21), resulting in -439. The available options don't match this result, suggesting an error in the question or choices.
Step-by-step explanation:
If s(x) = 2 - x² and t(x) = 3x, we need to find the value of (s∘t)(-7). The notation (s∘t)(-7) refers to the composition of the two functions, which means we first apply t to -7 and then apply s to the result of t(-7).
First, compute t(-7):
- t(-7) = 3(-7) = -21
Next, apply s to the result of t(-7):
- s(t(-7)) = s(-21)
- s(-21) = 2 - (-21)² = 2 - 441 = -439
None of the options A) 15, B) 18, C) 21, or D) 24 match -439, so there appears to be an error in the question or the options provided.